Assessing the Survey Dataset on Employment Status of Students before Graduates in Malaysian Public Higher Learning Institutions in Selangor - Abu, Roziya; Sayuti, Nazura Mohamed; Adam, Ainul Azreen bin; Keshminder, J. S.; Chuah, Soo- Cheng; Mohamed, Rahmat bin (Journal of Ecohumanism, 2024)
Employment status of student in Malaysian Public Higher Learning Institution play significant role in identified the marketability of university student in the industry. However, there are also a group of university students who began their employment before graduating from university. The increase of tuition fee charge, insufficient financial support, experience, and networking are the factor contributed towards the employment of student before graduation in Malaysian Public Higher Learning Institution, particularly in Selangor. Therefore, the purpose of this study to examine the employment status of student before graduates in various sector at Malaysian Public Higher Learning Institution in Selangor. The quantitative research approach has been adopted in exploring the topic of this study by using the survey dataset approaches. Almost 2,489 university students have participated in this study. The findings show 593 university students actively have occupations during their study either undergraduate or postgraduate student. Through the findings, the university student has actively sought the job opportunities before graduation in university for their livelihood especially after the post-pandemic Covid19 who affected all group of community particularly in Malaysia. The finding of this study will contribute to the government and private organizations to strategizing the action plan by providing the flexible time for the working student in adapting their study and career.